Angka kejadian kanker rongga mulut pada pasien Di RSUP Sanglah dengan riwayat merokok dan minum minuman beralkohol dalam periode januari 2015 – juni 2016 - Siddhi Putra, Gusti Agung Made; Setiawan, I Gede Budhi (E-Jurnal Medika Udayana; Vol 7 No 1 (2018): E-Jurnal Medika Udayana, 2018)
Based on several studies, smoking and drinking alcohol are considered as important risk factor of oral cancer development. The aim of this study is to find the incidence of oral cancer in RSUP Sanglah with history of smoking and/or drinking alcohol. Observational study using cross sectional descriptive study design with seconder data from medical records in RSUP Sanglah and using total sampling technic. The incidence of patient with history of smoking is 24%, patient with history of smoking and drinking is 4%, patient with history of betel chewing is 8%, and patient with history of betel chewing and smoking is also 8%. Conclusion: From this study can be concluded that in the field, data which is earned from medical record show the lowness of the oral cancer incidence in patient with history of smoking, drinking alcohol, and/or betel chewing compared to patient without those history (56%). Keywords: Oral cancer, incidence, smoking and drinking alcohol